The uses of Internet and the social media by the teachers’ unions in the context of the protest against the devaluation of the profession - Marques Alves, P. (IV ISA Forum of Sociology. Challenges of the 21st Century: Democracy, Environment, Inequalities, Intersectionality, 2021)
Employment relations in the Portuguese public administration have changed profoundly in recent years, firstly under the “New Public Management” ideology and later with the austerity policies. This hit hard the education sector, particularly teachers’ wages and careers. Much of this transformation was led by the previous right-wing government. With the change of the political situation after 2015, teachers thought that the process of devaluation of the profession will stop. Despite the replacement of the cuts in the wages, the actual government of the Socialist Party continues to refuse the full recovery of the length of service frozen (9 years, 4 months and 2 days) only accepting to recover slightly over two years. This situation led to a deep protest, which takes place both in the real and digital worlds. In this paper we intend to analyze how the teachers’ unions are using the Internet and the social media in the context of this protest. Our findings show that they are being used intensively, but with different purposes. Some unions used them mainly for mobilizing; others used them basically for information. However, there is a convergence in the fact that the use that it is made do not allow us to assert that unions have fundamentally changed the way they act in the Internet, namely in what concerns the enhancement of participation. A relative exception is STOP, a newly founded union. In this case, it takes advantage of the potential of the new media through the promotion of participation, for instance, by answering the questions or comments in Facebook.